Study on Productivity of Jhum Crops and Post-harvest Soil Nutrient Status by Using NPK Briquette - Zonayet, Md.; Paul, Alok Kumar (International Journal of Bio-resource and Stress Management, 2020)
The experiments were conducted at Bandarban hill district in Chittagong, Bangladesh during March, 2017 to November, 2017 to study the effect of NPK briquette on the growth and development of Jhum crops and examine of Jhum field soil by using NPK briquette. In this experiment, Jhum crops i.e. cucumber, maize, sweet gourd and chili were used as the test crop. The experiment was conducted in two fields designed on Randomized Completely Block Design (RCBD). The treatments consisted of 7(seven) levels of NPK briquette i.e. Control, 100% RFD (267.5 kg ha-1), 120% RFD (320.8 kg ha-1), 80% RFD (214.1 kg ha-1), 100% NPK briquette (267.5 kg ha-1), 120% NPK briquette (320.8 kg ha-1), 80% NPK briquette (214.1 kg ha-1). The highest yield of cucumber (912.6 kg ha-1), maize (846.2 kg ha-1), sweet gourd (1517.0 kg ha-1) and chili (187.7 kg ha-1) were found in 100% NPK briquette and for all cases lowest results were found in control treatment. Most of the time post-harvest soil of field-I and II contain higher organic matter (2.86%), organic carbon (1.70%), total nitrogen (0.087%), exchangeable K (0.14 meq 100 g-1), available Zn (0.66 µg g-1) in 100% NPK briquette (267.5 kg ha-1) and for all treatment lower organic matter (2.65 %), organic carbon (1.61%), total nitrogen (0.080%), exchangeable K (0.10 meq 100 g-1), available Zn (0.41 µg g-1) were found in control.